STATE OF THE INTERNAL ORGANS OF FETUS PREGNANCY SHR FEMALE RATS AT DIFFERENT PERIODS OF GESTATION - Toryanik, E.L. (World of Medicine and Biology, 2012)
This paper presents data on the effect of hypertension on the state of the internal organs of fetuses of pregnant SHR female rats at different periods of gestation. Found that pregnancy, which occurs on a background of hypertension, can lead to severe pathology of intrauterine growth retardation (increase in the size of the bladder, subcutaneous hematoma, and especially to the expansion of the ventricles of the brain and swelling of the subcutaneous tissue).